Pengalihan Saham atas Harta Bersama Tanpa Persetujuan Pasangan Kawin dalam Perseroan Terbatas - Qonita, Leilani Tertia; Setyono, Yoni Agus (Wajah Hukum, 2025)
Marriage has legal consequences regarding the presence of joint property. Shares, as part of the joint property, can be transferred to another party. However, the transfer of shares without the consent of one of the spouses, whether husband or wife, has the potential to cause legal issues. In the analysis, the Author uses the doctrinal research method, resulting in a descriptive-analytical writing style. The results of the research indicate that if one party, whether the husband or the wife, transfers shares in a Limited Liability Company that are part of the joint property without the consent of the other party, then the transfer is considered invalid and null and void by law because it is carried out by a party who does not have the authority. The notary has the right to refuse to create an authentic deed related to the transfer because such action violates the applicable legal provisions. If the creation of an authentic deed violates the applicable laws and regulations, the deed may be annulled, and the Notary may face sanctions for ethical violations, administrative sanctions, and civil penalties.